Comparison of marginal adaptation of fiber reinforced composite and metal ceramic full veneer crown - Hassan, Tareq; Ferdous, Sohana; Aurangjeb, Aslam Md (Bangladesh Journal of Dental Research & Education, 2015)
Fiber reinforcement was introduced to clinical dentistry for the first time in the 1960s when investigators attempted to reinforce polymethyl-methacrylate dentures with glass or carbon fibers. It has recently been shown that crowns, bridges and posts made of FRC can be used successfully in dental practice and on the basis of marginal adaptation they are more acceptable than conventional metal ceramic crown. A prospective comparative cross-sectional study was performed involving 60 patients who attended in the out patients department of Prosthodontics, Faculty of Dentistry, BSMMU during the period of January 2007 to December 2008. Clinical data were recorded for the selected 60 patients who were divided into two groups experimental and control. Marginal adaptation was indexed after California Dental Associations quality evaluation system. The age of the patients ranged from 18 to 42 years in group A and 17 to 38 years in group B. The highest number of patients was in the age group 21-30 years in both the groups. The mean age was 24.9±5.8 years and 25.0±4.8 years in group A and group B respectively. There were 26 male and 34 female patients in the study and male female ratio was 1:1.3. In group A patients, 12(40.0%) were male and 18(60.0%) female. In group B patients 14(46.7%) were male and 16(53.3%) were female. After 4 months all the patients were in grade I in both the groups. After 8 months all the patients were in grade I in group A and 27(90.0%) patients in grade I in group B. After 12 months all the patients were in grade I in group A and 25(83.3%) patients were in grade I in group B. The difference was not statistically significant (p>0.05) after 8 months, however after 12 months the difference was significant (p<0.05). The Fiber Reinforced Composite crown represents a valuable development in the field of Prosthetic Dentistry. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22450 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 01-05